Analytic rubrics for the practical assessment of students’ performances in engineering survey course / Adnan Derahman, Nur’Ain Mat Yusof and Noorfaizah Hamzah - Derahman, Adnan; Mat Yusof, Nur’Ain; Hamzah, Noorfaizah (2024)
The use of analytic rubrics as an assessment tool has been an integral component of education. In Surveying courses, it is essential to evaluate the psychomotor skills under simulated conditions of actual practise. The main objective of this study is to determine the comparative and efficacy of practical assessment conducted at the diploma and degree levels in the Civil Engineering programme. In order to achieve the objective, implementing rubrics in the continuous assessment of the Surveying courses to facilitate a profound comprehension of physics, mathematics, and engineering principles needs to be executed. Previously, a practical assessment has been conducted in a traditional method which gauges the student performance according to the time records during certain practical tasks given resulting in inadequate assessment tools that failed to capture the psychomotor component of practical assessments effectively. As for methodology, a comparative analysis was conducted to examine the consistency and usefulness of analytic rubrics in assessing the course and program outcomes of Surveying courses at both diploma and degree levels. The analysis aimed to determine the impact of these rubrics on student performance. This comparison should be conducted in order to prevent redundant actions, as it pertains to diploma level students who will be integrated into the degree program. This assessment reveals that most students met all performance criteria at an acceptable level. This indicates that the analytical rubric used for the Practical Test in Surveying courses is adequate and effective as a grading instrument. As for the results, the comprehensive analysis indicates that a significant majority, ranging from 75% to 81%, exhibited commendable performance in achieving the criteria for various Programme Outcomes (PO), particularly in PO4, PO5, PO9, and PO10.